(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Thedifferent weights attached to the different indicators or parameters of creditquality have been allotted on the basis of the expert opinion of a number ofbank managers, economists, experts and consultants. The expert group consistingof 61 respondents was requested to provide leading indicators/parameters ofcredit quality and attach numerical weights to each parameter on the basis oftheir importance in the overall credit quality index. The experts were agreedon the six parameters and suggested weighting pattern based on their bankingexperience and expertise. Except in a few cases the weights attached todifferent parameters varied by small to moderate margins. The different weightswere then averaged and used as the benchmark for the purpose of subsequentanalysis. This method of computing the composite index was widely accepted asit reflected a practical and reasonable benchmark for the region in which thisstudy was conducted.